In silico study of beta citronellol compound in lime plant (Citrus aurantifolia) as a drug candidate for enterovirus disease - Early Maulina; Tanto Situmorang (Universitas Muhammadiyah Malang, 2025)
Background: Human Enterovirus is an RNA virus affecting millions globally, particularly children, causing a range of symptoms from mild to severe, including serious conditions like meningitis and AFP. Current synthetic treatments have side effects, necessitating the exploration of natural alternatives. Lime (Citrus aurantifolia) is a potential candidate. Objectives: To determine the potential of the beta citronellol compound found in lime (Citrus aurantifolia) as an inhibitor of enterovirus activity in in-silico study. Methods: This research employed an in-silico method. This involved analyzing the bioactivity potential of beta citronellol, assessing its bioavailability and toxicity, and performing molecular docking. Data was sourced from PubChem and RSCB PDB. Bioactivity probability was predicted using PASS Online. Virtual screening was conducted via molecular docking with PyRx. Visualization was performed using PyMol and Discovery Studio. Results: The toxicity prediction and molecular docking analysis of beta citronellol against the 3J3Z protein indicated that this compound has a high and specific potential as a receptor candidate for the enterovirus target. Conclusion: The findings of this in silico study suggest that the beta citronellol compound possesses good antiviral activity against enteroviruses.